Radiographic Response of Vessel Involvement and Resectability After Neoadjuvant Chemoradiation in Patients With Locally Advanced Pancreatic Cancer. (November 2020) - Naumann, Patrick; Ottensmeier, Friederike; Farnia, Benjamin; Ben-Josef, Edgar; Liermann, Jakob; Maier-Hein, Klaus H.; Hackert, Thilo; Debus, Jürgen
Abstract : Objectives: Survival of patients with locally advanced pancreatic cancer (LAPC) is improved when neoadjuvant chemoradiation enables subsequent surgical resection. Here, the authors assess changes in vessel involvement as a possible indicator of resectability. Methods: Pancreatic gross tumor and all major abdominal vessels were contoured for 49 patients with unresectable LAPC before and after neoadjuvant chemoradiation. Changes were compared by paired t tests. Tumor-vessel relationships were automatically quantified using Medical Imaging Interaction Toolkit and examined for correlation with resectability and outcome. Results: Tumor volumes were significantly reduced by chemoradiation (41 to 33 mL, P <0.0001). Maximum circumferential vessel involvement decreased for most patients and was statistically significant for the superior mesenteric ( P <0.003) and splenic veins ( P <0.038). Resection was possible in some patients and correlated positively with survival (28 vs. 15 mo, r =0.40), a decrease in CA 19.9 levels ( r =0.48), and reduced involvement of most vessels. Nevertheless, surgical resection with a successful detachment of tumor tissue from major vessels was also achieved in some patients who did not show improvement in radiographic vessel involvement, but rather a reduction in tumor volume and CA 19.9 levels. Conclusions: The present analysis demonstrates that neoadjuvant chemoradiation can enable subsequent surgical resection in patients with LAPC. Complete resection substantially prolongs survival. Therefore, surgical exploration should be offered if vessel involvement is improved by chemoradiation and considered in radiographic unchanged vessel involvement if size and CA 19.9 levels decrease, as these factors may indicate resectable disease, too.